Effet de quelques paramètres physico-chimiques sur lecycledevied'unmicro-crustacée(Daphniamagna) - Djellabi Aya (My University, 2025)
Theobjectiveofthisstudyistoevaluatethechroniceffect ofsalinityand pHonthe Survival, growth, and reproduction ofa micro crustacean (Daphnia magna). To carryout this study, daphnia were exposed for 21 days to different concentrations Of salinity (control 0.4‰; C1: 2‰; C2: 3‰) and different pH values (Control: 7.22; basic: 11.37; acidic: 4.23) The results obtained reveala reduction inthe various life cycle parameters of Daphnia magna (survival, growth, longevity, egg size, size of adult females at first reproduction). These parametersdecreasewithhighsalinityconcentrations(C1: 2‰;C2:3‰)and increasewiththe control(0.4‰). Withregard to pH, it isalso notedthat inthecontrol, wherethepH isalkaline (7.22), the biological parameters are positive, whereas the acidic pH (4.23) reduces the life cycle of the species studied, while the basic pH (11.37) is lethal with a longevityof 0%. --------------------------------------------------------------------------------------------------------------------------- الهدفمنهذاالعملهوتقييمالتأثيرالمزمنللملوحةودرجةالحموضةعلىالبقاءوالنمووالتكاثرلدىأحدأنواعالقشرياتالدقيقةmagna).(Daphniaلإجراءهذاالعمل،تمتعريضالدافنيالمدة21يومًالتركيزاتمختلفةمنالملوحة)الشاهد ‰0.4؛2‰C1:؛3‰(C2:وقيممختلفةمنالرقمالهيدروجيني)الشاهد:7.22؛القاعدية:11.37؛الحمضية:(4.23تكشفالنتائجالتيتمالحصولعليهاعنانخفاضفيمختلفمعاييردورةحياةدافنياماغنا)البقاءعلىقيدالحياة،والنمو، وطولالعمر،وحجمالبيض،وحجمالإناثالبالغةعندالتكاثرالأول.(تنخفضهذهالمعاييرمع ارتفاعتركيزاتالملوحة2‰)C1:؛3‰(C2:وتزدادمعالشاهد.(0.4‰)فيمايتعلقبدرجةالحموضة،نلاحظأيضًا أنالشاهدالذيتكونفيهدرجةالحموضةقلوية(7.22)تكونالمعلماتالبيولوجيةفيالاتجاهالصحيح،بينماتقللدرجةالحموضةالحمضية(4.23)مندورةحياةالأنواعالمدروسة،أمادرجةالحموضةالقاعدية(11,37)فهيقاتلةمعطول عمريبلغ0٪. ---------------------------------------------------------------------------------------------------------------------------- L’objectifdecetravailconsisteàévaluer l’effet chroniquede lasalinité et dupHsurla Survie, la croissance et la reproduction d’une micro-crustacée (Daphnia magna). Pourlaréalisationdecetravailonaexposé ladaphniependant 21joursàdesconcentrations différentes de salinité (Témoin 0.4‰ ; C1 : 2‰ ; C2 :3 ‰) et des valeurs distinctes du pH (Témoin : 7,22 ; basique : 11,37 ; acide : 4,23) Lesrésultatsobtenusrévèlent uneréductionpourlesdifférentsparamètresdecycledeviede Daphnia magna (la survie, la croissance, la longévité, la grandeur de ponte, la taille des femelles adultes à la première reproduction). Ces paramètres diminuent avec les concentrations élevées de salinité (C1 : 2‰ ; C2 :3 ‰) et augment avec le témoin (0.4‰). Concernant le pH onnote aussique le témoinoù le pH est alcalin (7,22) les paramètres biologiqueest danslebonsensparcontreledupHacide(4,23)réduit lecycledeviede l’espèce étudiée, le pH basique (11,37) est létale avec une longévité de 0%.
Keywords: Daphniamagna; chronictest; Salinity; pH; Reproduction; Lifecycle دافنياماغنا،اختبارمزمن،ملوحة،درجةالحموضة،تكاثر،دورةحياة. Daphniamagna; Testchronique; Salinité; Cycledevie.